The influence of brand Image on the competitiveness of local products at jawet niang small and medium enterprises with purchasing decisions as a mediating variable - Inglesia, Nathaly; Kristinae, Vivy; Muliyani, Agustina; Retawati, Anike (Institute of Computer Science (IOCS), 2025)
Using purchase decision as a mediating variable, this study attempts to examine how brand image affects local product competitiveness in IKM Jawet Niang. Using a quantitative technique, the study was carried out in Palangka Raya City with an emphasis on a local small and medium industry (IKM). Customers who had made at least two purchases from IKM Jawet Niang were given questionnaires to complete in order to gather data. SmartPLS 4.1 was used for data processing, and 96 people made up the sample. The findings show that brand image has a favourable impact on both product competitiveness and purchase decisions, with the relationship between brand image and product competitiveness being mediated by purchase decisions. This study adds to the body of knowledge on traditional-cultured local SMEs, stresses the value of brand awareness in boosting the competitiveness of local products, and highlights how SMEs support regional economic growth while preserving ancestral culture by empowering local speciality products